Short communication. Genotyping and phylogenetic analysis of bovine viral diarrhea virus (BVDV) isolates in Kosovo - Izedin Goga; Kristaq Berxholi; Beqe Hulaj; Driton Sylejmani; Boris Yakobson; Yehuda Stram (Veterinaria Italiana, 2014)
Three serum samples positive in Antigen ELISA BVDV have been tested to characterise genetic diversity of bovine viral diarrhea virus (BVDV) in Kosovo. Samples were obtained in 2011 from heifers and were amplified by reverse transcription-polymerase chain reaction, sequenced and analysed by computer-assisted phylogenetic analysis. Amplified products and nucleotide sequence showed that all 3 isolates belonged to BVDV 1 genotype and 1b sub genotype. These results enrich the extant knowledge of BVDV and represent the first documented data about Kosovo BVDV isolates.